2009
DOI: 10.1111/j.1525-142x.2008.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

The deep evolution of metazoan microRNAs

Abstract: microRNAs (miRNAs) are approximately 22-nucleotide noncoding RNA regulatory genes that are key players in cellular differentiation and homeostasis. They might also play important roles in shaping metazoan macroevolution. Previous studies have shown that miRNAs are continuously being added to metazoan genomes through time, and, once integrated into gene regulatory networks, show only rare mutations within the primary sequence of the mature gene product and are only rarely secondarily lost. However, because the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
572
2
12

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 511 publications
(621 citation statements)
references
References 82 publications
35
572
2
12
Order By: Relevance
“…Moreover, we also observed that a small fraction of novel miRNA emerged at different time points are copies of members of ancestral families except for metazoan and human-specific. The emergence of these new miRNA genes which are copies of members of ancestral families could be due to genome duplication events (GDEs), including the occurrence of tandem duplications and non-local duplications, which increased diversity of miRNA genes [22]. Further analysis revealed that a large portion of novel human miRNA genes emerged at different time points are copies of new families, suggesting that novel miRNA genes often experience genome duplication events.…”
Section: Evolutionary Distribution Of Human Mirnasmentioning
confidence: 99%
“…Moreover, we also observed that a small fraction of novel miRNA emerged at different time points are copies of members of ancestral families except for metazoan and human-specific. The emergence of these new miRNA genes which are copies of members of ancestral families could be due to genome duplication events (GDEs), including the occurrence of tandem duplications and non-local duplications, which increased diversity of miRNA genes [22]. Further analysis revealed that a large portion of novel human miRNA genes emerged at different time points are copies of new families, suggesting that novel miRNA genes often experience genome duplication events.…”
Section: Evolutionary Distribution Of Human Mirnasmentioning
confidence: 99%
“…The evolutionary process of microRNA is slower even than the most conserved genes in the metazoan genome (GrimsonSrivastava et al, 2008;Wheeler et al, 2009). Therefore, it is possible for microRNA families to be used in tracking the evolutionary origin of the most ancient animal phylogeny.…”
Section: Discussionmentioning
confidence: 99%
“…Other ways that new miRNAs can arise include the modification or duplication of pre-existing miRNAs [108]. A rapid increase in the diversity of miRNAs in existing genomes is often correlated to a burst of new morphological diversity, and thus miRNA may be crucial to the development of complex morphologies because of its regulatory activity [71,110,134].…”
Section: Evolution Of Mirnamentioning
confidence: 99%
“…Once an miRNA has gained a function, it rarely is lost from the genome [108,110]. Because older miRNAs evolve at a very low rate, and as a result are well conserved, they can be used as excellent phylogenetic markers [134].…”
Section: Evolution Of Mirnamentioning
confidence: 99%